Factorial invariance, scale reliability, and construct validity of the job control and job demands scales for immigrant workers: The Multi-Ethnic Study of Atherosclerosis (MESA) - Fujishiro, Kaori (2011)
Immigrants have a different social context from those who stay in their home country or those who were born to the country that immigrants now live. Cultural theory of risk perception suggests that social context influences one’s interpretation of questionnaire items. We examined psychometric properties of job control and job demand scales with US- and foreign-born workers who preferred English, Spanish, or Chinese (n=3114, mean age=58.1). Across all groups, the job control scale had acceptable Cronbach’s alpha (0.78–0.83) and equivalent factor loadings (ΔCFI<0.01). Immigrants had low alpha (0.42–0.65) for the job demands scale regardless of language, education, or age of migration. Two job-demand items had different factor loadings across groups. Among immigrants, both scales had inconsistent associations with perceived job stress and self-rated health. For a better understanding of immigrants’ job stress, the concept of job demands should be expanded and immigrants’ expectations for job control explored. (149/150 limit)